Material Incentives as Practice during Interaction between the Russian Empire and Kazakh Elite of the Junior and Middle Hordes in the 18th - First Half of the 19th Century - Lysenko, Yuliya A.; Gundova, Olga E. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
Through their study, the authors analyze the forms of material incentives used by the authorities of the Russian Empire in relations with the Kazakh elite of the Junior and Middle Hordes in the 18th - first half of the 19th century. The purpose is to reconstruct the various forms of material incentives used by the authorities of the Russian Empire in their relations with the Kazakh elite of the Junior and Middle Hordes in the 18th - first half of the 19th century and to identify the effectiveness of these practices. The source base of the study is published materials, as well as archival documents of the Russian State Historical Archive and the Central State Archive of the Republic of Kazakhstan. It is shown that the material incentives for Kazakhs by the imperial administration were carried out in various forms: presentation of valuables and money in the form of gifts and awards, assignment of salaries, pensions for service, construction of residential buildings, and trips to the Russian imperial court. The authors conclude that these practices found support among the Kazakh elite and became the norm of its relations with Russia. In this way, the Kazakh elite was integrated into the Russian sociolegal field, and at the same time, an ethnosocial stratum loyal to the imperial authorities was gradually formed.